On-call service: the role of chemical pathologists. - Neithercut, W D (1989)
The workload of the chemical pathology advisory on-call service was investigated. Over three years 317 calls were recorded, giving a mean of nine calls a month. Seasonal variation in the number of calls was observed, with an increase in calls during December, January, and February. Requests for the arrangement of analysis accounted for 231 calls, while there were 98 requests for advice. Authorization of a request for analysis was the outcome of 156 calls. Advice with respect to investigation, treatment, or interpretation of results was offered during 173 calls. The acute medical and surgical wards, the accident and emergency department, renal unit and intensive care unit accounted for 198 of the calls. The two analyses most frequently requested, through the advisory on-call service, were serum digoxin and blood ethanol, with 51 and 33 requests, respectively. The "acute" wards and accident and emergency department had the greatest request rate, accounting for 35 of the requests for digoxin and 26 of the requests for blood ethanol. The acute care areas were responsible for the major part of the workload, and a clinical requirement for the services of chemical pathologists out of hours, was observed.